Serum hormone and myocellular protein recovery after intermittent runs at the velocity associated with VO2max - Vuorimaa, T.; Vasankari, T.; Mattila, K.; Heinonen, O.; Häkkinen, K.; Rusko, H. (European Journal of Applied Physiology, 1999)
The present findings suggest that a single 28-min intermittent middle-distance running exercise does not induce changes in serum hormones of well-trained runners during recovery over 3 days, while changes in S-CK, CMJ and RPE15 km · h-1 indicate that 2-3 days of light training may be needed before the recovery at muscle level is complete.